Exploring diel vertical migration and spatiotemporal variation of zooplankton backscattering strength using an acoustic Doppler current profiler instrument in the Halmahera Sea, Indonesia - Maharani, Gabriella Rosya; Pujiyati, Sri; Solikin, Steven; Jaya, Indra; Adrianto, Dian; Mulyadi, Dikdik Satria; Dwinovantyo, Angga (Archives of Biological Sciences, 2024)
Paper description: To examine the characteristics of zooplankton distribution in the Halmahera Sea, Indonesia, an acoustic Doppler current profiler (ADCP) that can detect the presence and behavior of zooplankton spatially and temporally from deep to near-surface sea was used. Obtained ADCP data were converted to decibels using sonar equations. Acoustic data showed zooplankton’s diel vertical migration (DVM) pattern, with downward migration starting before sunrise and upward before sunset. High acoustic backscatter values were not attributed to a single zooplankton species. ADCP is an effective tool for detecting the presence and behavior of zooplankton by providing broad coverage with high-resolution data. Abstract: Given its critical role in marine ecosystems, this study comprehensively examined zooplankton distribution and behavior in the Halmahera Sea. The temporal and spatial dynamics of zooplankton acoustic backscatter values were analyzed using a 153.6 kHz vessel-mounted acoustic Doppler current profiler (ADCP). Analysis was supplemented by biological sampling with a bongo plankton net. Further evaluation included the analysis of oceanographic and bathymetric data. The acoustic, oceanographic, and biological sampling data were obtained from the Jala Citra I “Aurora” survey expedition in 2021, while the bathymetry data were obtained from the General Bathymetric Charts of the Ocean (GEBCO). The raw ADCP data, represented as digital counts, were transformed into mean volume backscattering strength (MVBS) expressed in decibels (dB) using sonar equations to yield a measure proportional to zooplankton biomass. Temporal observations revealed a diel vertical migration (DVM) pattern in zooplankton aggregation, characterized by movements responding to the daily solar cycle. Spatial observations indicated a higher zooplankton density in semi-enclosed waters than in open water. The high values of acoustic backscatter are not attributed to a single species of zooplankton. Biological sampling identified that Oncaea spp. and Oithona spp., a species from the Cyclopoida order, exhibit the highest abundance. The study concludes that the ADCP, based on acoustic backscatter measurements and data sampling, is an effective tool for detecting the presence and behavior of zooplankton.